Molecular circuit for exponentiation based on the domain coding strategy - Huang, Chun; Duan, Xiaoqiang; Guo, Yifei; Li, Panlong; Sun, Junwei; Shao, Jiaying; Wang, Yanfeng (Frontiers in Genetics, 2024)
DNA strand displacement (DSD) is an efficient technology for constructing molecular circuits.However, system computing speed and the scale of logical gate circuits remains a huge challenge.In this paper, the new method of coding DNA domains is proposed to carry out logic computation.The structure of DNA strand is designed regularly, and the rules of domain coding are described.Based on this, multiple inputs and one output logic computing modules are built, which is the basic components for building digital circuits. If the module has n inputs, it can implement 2 n logic functions, which reduces the difficulty of designing and simplifies the structure of molecular logic circuits. In order to verify the superiority of this method for developing large-scale complex circuits, the square root and exponentiation molecular circuits are built. Under the same experimental conditions, compared with the dual-track circuits, the simulation results show that the molecular circuits designed by domain coding strategy has faster response time, simpler circuit structure, better parallelism and scalability. The method of forming digital circuits based on domain coding provides a more effective way to realize intricate molecular control system and promotes the development of DNA computing.